OPTIMASI PROSES PEMBUATAN KARAGINAN DARI RUMPUT LAUT MERAH (Euchema cottonii) - Fifi Arfini (JURNAL GALUNG TROPIKA, 2013)
The purpose of this study is to assess and optimize the process of extraction of carrageenan (variation ratio of water, the concentration of KCl precipitation and temperature) on the seaweed Eucheuma cottonii to shorten the processing time. This research method is divided into two stages: 1) Preliminary research with the aim to find a range of concentrations of KCl solution is best, 2) optimization of the process is to compare the water phase, the concentration of KCl precipitation and temperature are optimal. Carrageenan is then analyzed yield (AOAC. 1984), viscosity (FMC Corp. 1977), power gel (FMC Corp. 1977), moisture content (AOAC 1995), ash (AOAC 1995), acid insoluble ash content (AOAC 1995), the levels of sulfate (FMC Corp. 1977) and whiteness (Food Chemical Codex. 1981). Experimental design used was completely randomized factorial design. Preliminary results show The concentration of KCl solution 1 and 1.5% selected the best, although the structure is not harder than 2% KCl but not to cause a sense of the carrageenan produced. Produced the highest yield of water ratio 1:40. Highest viscosity ratio obtained in the combination treatment of water 1:20, 1% KCl. Carrageenan gel strength generated in this study ranged between 1493.49 - 2202.97 g/cm2 at each combination of treatments. Combination treatments are best produced water ratio 1: 20, 1% KCl concentration and precipitation temperature of 30 oC (A1B1C2) based on the parameters yield of 31.77%, 145.00 cP viscosity, gel strength 1897.14, 9.73 moisture content, ash content of 29.59, ash content was 0.83 acid soluble, sulfate levels and whiteness 18:36 51.57. Research on the optimization process can still be studied better, especially in the financial analysis.